2016
DOI: 10.4143/crt.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Treatment Initiation Does Not Adversely Affect Survival Outcome in Breast Cancer

Abstract: PurposePrevious studies examining the relationship between time to treatment and survival outcome in breast cancer have shown inconsistent results. The aim of this study was to analyze the overall impact of delay of treatment initiation on patient survival and to determine whether certain subgroups require more prompt initiation of treatment.Materials and MethodsThis study is a retrospective analysis of stage I-III patients who were treated in a single tertiary institution between 2005 and 2008. Kaplan-Meier s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 13 publications
6
29
0
2
Order By: Relevance
“…Delays in making diagnosis and starting treatment have been associated with worse prognosis and decreased survival 5 . Delays between disease suspicion and first appointment with a cancer specialist are often associated with pa-tient´s characteristics, such as old age, low level of education, lack of information about the disease, lack of health insurance coverage and lack of financial resources to afford medical services [7][8][9] . On the other hand, delays in the intervals between appointment, diagnosis and treatment are often related to the healthcare context 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Delays in making diagnosis and starting treatment have been associated with worse prognosis and decreased survival 5 . Delays between disease suspicion and first appointment with a cancer specialist are often associated with pa-tient´s characteristics, such as old age, low level of education, lack of information about the disease, lack of health insurance coverage and lack of financial resources to afford medical services [7][8][9] . On the other hand, delays in the intervals between appointment, diagnosis and treatment are often related to the healthcare context 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have shown benefits for decreased wait times to surgery 1,2 , but other studies have contradicted those results 3 . Yoo et al 3 reported that delay in treatment initiation did not adversely affect survival in bca, but their study looked only at a time to surgery of up to 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported varying results for the effect of diagnostic and treatment wait times on breast cancer (bca) outcomes [1][2][3] . Systematic reviews have suggested that a benefit accrues from shortening wait times, and their conclusions recommend minimizing delays to diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have investigated the association between time from breast cancer diagnosis to first treatment and survival are inconclusive, [14][15][16][17][18][19][20][21] possibly owing to differences in calendar periods, study populations, cut-offs and starting (e.g., physician referral vs. morphological diagnosis) and end (e.g., surgery vs. neoadjuvant therapy) points for calculating delays. The two, to date, largest studies, both published by Bleicher et al 19 have found an association between increased time to surgery and worse survival.…”
Section: Introductionmentioning
confidence: 99%